The Impact of Multimedia Learning Models on Listening Comprehension: A Systematic Review of Self-Efficacy and Technology Integration - Saraswaty, Dwi Rara; Adawiyah, Dita; Sulistiyo, Urip; Haryanto, Eddy (PPSDP International Journal of Education, 2024)
The purpose of this systematic review is to examine the impact of multimedia learning models on listening comprehension, with a particular focus on the roles of self-efficacy and technology integration. The study utilizes the PRISMA methodology to ensure rigor in the systematic review process, synthesizing research findings from 2019 to 2024. Results show that multimedia learning models significantly improve listening comprehension by providing diverse and engaging methods, aligning with Mayer’s cognitive theory of multimedia learning. Additionally, self-efficacy and technology integration were identified as critical moderating factors, enhancing both learning outcomes and learner confidence. This review contributes to the development of effective multimedia learning environments, offering valuable insights for educators, instructional designers, and policymakers.